O bando soberano, o abandono e a fome : uma análise a partir de Giorgio Agamben - Nicoli, Sabrina Augusto (2023)
Based on the conceptions of the philosopher Giorgio Agamben, especially in the first Homo Sacer of the philosophical project, Il Potere Sovrano e La Nuda Vita, this text seeks to understand abandonment based on the sovereign decision. Schmitt's decisionism was developed in the midst of the philosopher's political activism during Nazism, the regime that produced the Musselman, the true witness. In this text, a detailed study will be made of the Musselman, as well as his relationship with the homo sacer of Roman Law and the wargus, coming from the Salian Franks through the Salic Law. These analyzes will be the basis for exposing some phenomena of abandonment. Judith Butler brings a critique of bare life that becomes universal, ending up understanding that it is in precarious life that true abandonment occurs. The sovereign band opens the field and another power emerges beneath the precarious life, also subjugating it. One of the characteristics of sovereign power is to seek to regulate aspects ofsociety such as life, death, purchasing power, and also hunger. Hunger will be studied in consideration of Ramón Turró's theses, but as a desire for desecration, which places limits on sovereign power over life